2006
DOI: 10.1007/s00213-006-0549-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired performance of alpha7 nicotinic receptor knockout mice in the five-choice serial reaction time task

Abstract: Rationale Nicotinic receptors have been implicated in attentional performance. Nicotine can improve attention in animals and humans, but knowledge about relevant receptor subtypes is very limited. Objectives The aim was to examine the role of α7 receptors in attentional performance of mice and in effects of nicotine. Materials and methods Mice with targeted deletion of the gene coding for the α7 subunit of nicotinic receptors and wild-type controls were trained on a five-choice serial reaction time task with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 40 publications
(71 reference statements)
8
114
1
3
Order By: Relevance
“…It has been considered that patients consume tobacco for their self-medications due to its nicotine content. It was also demonstrated that α7 NAChR knock-out mice showed worse performance than wild-type animals in cognitive tasks [16]. These data have indicated that α7 NAChR dysfunction can be responsible for schizophrenia pathophysiology and a new drug target for the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 88%
“…It has been considered that patients consume tobacco for their self-medications due to its nicotine content. It was also demonstrated that α7 NAChR knock-out mice showed worse performance than wild-type animals in cognitive tasks [16]. These data have indicated that α7 NAChR dysfunction can be responsible for schizophrenia pathophysiology and a new drug target for the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 88%
“…Of particular relevance to attentional and sensory gating deficits in schizophrenia (Adler et al, 1998;Heinrichs, 2005;Lubow, 2005), a7-nAChR agonists alleviate both types of deficits in humans and animals Olincy et al, 2006;Timmermann et al, 2007;Wishka et al, 2006). A role for the a7-nAChR in these processes is supported by findings that a7-nAChR knock-out mice show attentional and gating impairments (Adams et al, 2008;Hoyle et al, 2006;Young et al, 2004Young et al, , 2007. Finally, there is a diminished expression of a7-nAChR in the hippocampus and frontal cortex in schizophrenia (Freedman et al, 1995;Guan et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…However, genetic approaches assessing the role of nAChRs have shown that α7* receptors do have a role in attention. Knockout mice lacking the gene for the α7 nAChR subunits showed impaired task acquisition and a higher rate of omissions in the 5-choice serial reaction time task [45,46]. Since the mice used for these studies lacked α7* nAChR expression throughout their brains, it is not known whether the impairment in 8 attention performance was attributable to the lack of α7* receptors specifically in the PFC, let alone whether the effects were attributable to a specific type of cells in the PFC neuronal circuits.…”
Section: Nicotinic Achrs In the Pfcmentioning
confidence: 99%